Modelling of size and shape of damage zone in quasi-brittle notched specimens – analytical approach based on fracture-mechanical evaluation of loading curves (Fracture and Structural Integrity, 2016)
An analysis focused on capturing the phenomenon of quasibrittle fracture is presented. Selected parameters relevant for quasi-brittle fracture are evaluated and an assessment of their dependence on the size and shape of the test specimen is studied. Determination of these fracture characteristics is based on the records of the fracture tests on notched specimens, particularly from recorded loading diagrams. A method of separation of the energy amounts released for the propagation of the (effective) crack and that dissipated within the volume of a large nonlinear zone at the crack tip – the fracture process zone – is introduced and tested on selected data from experimental campaigns published in the literature. The work is accompanied with own conducted numerical simulations using commercial finite element code with implemented cohesive crack model. Results from three-point bending tests on specimens of different sizes and relative notch lengths are taken into account in this study. The proposed model has only two parameters whose values are constant for all specimen sizes and notch lengths.
Keywords: Quasi-brittle Fracture; Loading Curve; Work of Fracture; Resistance Curve; Effective Crack; Fracture Process Zone